2006
DOI: 10.1080/10401230600801176
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Aripiprazole in Treatment-Resistant Bipolar Depression

Abstract: Aripiprazole appeared effective and generally well tolerated in treatment-resistant bipolar depression. Controlled trials are warranted to systematically explore these preliminary naturalistic observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Since preliminary studies with aripiprazole showed benefit in the treatment of bipolar depression, future studies evaluating aripiprazole, using more conservative dosing regimens, are needed to further elucidate its role for this indication. [35][36][37] The primary limitation of our study was its retrospective design, which permitted only data previously recorded in patient charts to be included in the analysis. Thus, limited information on the rationale for product selection, reason(s) for treatment discontinuation, and duration and severity of illness was available.…”
Section: Discussionmentioning
confidence: 99%
“…Since preliminary studies with aripiprazole showed benefit in the treatment of bipolar depression, future studies evaluating aripiprazole, using more conservative dosing regimens, are needed to further elucidate its role for this indication. [35][36][37] The primary limitation of our study was its retrospective design, which permitted only data previously recorded in patient charts to be included in the analysis. Thus, limited information on the rationale for product selection, reason(s) for treatment discontinuation, and duration and severity of illness was available.…”
Section: Discussionmentioning
confidence: 99%
“…16,[21][22][23][24][25][26][27][28][29] Furthermore, aripiprazole also demonstrated a low potential for weight gain when used as adjunctive treatment in patients with bipolar mania 29 or bipolar depression. 30 It is possible that concomitant prescription of aripiprazole with antidepressants may increase risk of weight gain. It is important to note that, even in this population already at risk for metabolic disturbance (more than 50% of patients had a baseline body mass index > 30 kg/m 2 ), change in weight did not translate into a worsening of metabolic parameters, such as lipid or glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…There have been six open-label case studies of aripiprazole augmentation in bipolar depression (Ketter et al 2006; Kemp et al 2007; McElroy et al 2007; Dunn et al 2008; Sokolski 2007; Mazza et al 2008). Three of the studies were retrospective chart reviews of patients with treatment-resistant depression (Ketter et al 2006; Kemp et al 2007; Sokolski 2007), and all but one study included both bipolar I and II patients (Sokolski 2007).…”
Section: Discussionmentioning
confidence: 99%